Nature and evoked culture: Sex differences in personality are uniquely correlated with ecological stress. (1st October 2019) - Kaiser, Tim
Abstract: Sex differences in personality were found to be larger in more developed and more gender-equal societies. However, the studies that report this effect either have methodological shortcomings or do not take into account possible underlying effects of ecological variables. Here, a large, multinational (N = 867, 782) dataset of personality profiles was used to examine sex differences in Big Five facet scores for 50 countries. Gender differences were related to estimates of ecological stress as well as socio-cultural variables. Using a regularized partial-correlation approach, the unique associations of those correlates with sex differences were isolated. Sex differences were large (median Mahalanobis' D  = 1.97) and varied substantially across countries (range 1.49 to 2.48). Global sex differences are larger in more developed countries with higher food availability, less pathogen prevalence, higher gender equality and an individualistic culture. After controlling for confounds, only cultural individualism, historic pathogen prevalence and food availability remained. Sex differences in personality are uniquely correlated to ecological stress. Previously reported correlations between greater sex differences and socio-cultural liberalism could be due to confounding by influences of ecological stress.